Ressignificando o casamento: a evolução do matrimônio como base primordial da entidade familiar - Gozzi, Camila Monzani (2020)
From the dawn of life in society, humanity has come together in groups according to their common affinities and ancestors, thus giving rise to what we today call family. Over the years, with the intention of continuing the family groups that were formed and thus preserving their identity, territory and heritage, the individuals who formed them began to unite with each other and with other formations — and did so through marriage. Surrounded by countless moral, social, formal, religious and even dogmatic aspects and yet practiced worldwide nowadays, marriage has gone through a tremendous transformation during these years, so it can be seen today — and betting for the future — the effective process of restructuring and reframing its concept itself. This paper aims to analyze, through research on doctrinal lessons and positions of jurisprudence, the evolution of this process accompanied by the emergence of other family entities also constitutionally recognized by the Brazilian rule and, finally, the position of foreigner doctrine and jurisprudence, especially considering countries where marriage faced a similar process of resignification